Herbivore biocontrol and manual removal successfully reduce invasive macroalgae on coral reefs - Neilson, Brian J.; Wall, Christopher B.; Mancini, Frank T.; Gewecke, Catherine A. (PeerJ, 2018)
Invasive macroalgae pose a serious threat to coral reef biodiversity by monopolizing reef habitats, competing with native species, and directly overgrowing, and smothering reef corals. Several invasive macroalgae (Eucheuma clade E, Kappaphycus clade A and B, Gracilaria salicornia, and Acanthophora spicifera) are established within Kāne‘ohe Bay (O‘ahu, Hawai‘i, USA), and reducing invasive macroalgae cover is a coral reef conservation and management priority. Invasive macroalgae control techniques, however, are limited and few successful large-scale applications exist. Therefore, a two-tiered invasive macroalgae control approach was designed, where first, divers manually remove invasive macroalgae (Eucheuma and Kappaphycus) aided by an underwater vacuum system (“The Super Sucker”). Second, hatchery-raised juvenile sea urchins (Tripneustes gratilla), were outplanted to graze and control invasive macroalgae regrowth. To test the effectiveness of this approach in a natural reef ecosystem, four discrete patch reefs with high invasive macroalgae cover (15–26%) were selected, and macroalgae removal plus urchin biocontrol (treatment reefs, n = 2), or no treatment (control reefs, n = 2), was applied at the patch reef-scale. In applying the invasive macroalgae treatment, the control effort manually removed ∼19,000 kg of invasive macroalgae and ∼99,000 juvenile sea urchins were outplanted across to two patch reefs, totaling ∼24,000 m2 of reef area. Changes in benthic cover were monitored over 2 years (five sampling periods) before-and-after the treatment was applied. Over the study period, removal and biocontrol reduced invasive macroalgae cover by 85% at treatment reefs. Our results show manual removal in combination with hatchery raised urchin biocontrol to be an effective management approach in controlling invasive macroalgae at reef-wide spatial scales and temporal scales of months to years.
Keywords: Invasive species; Biocontrol; Macroalgae; Kaneohe bay; Kappaphycus; Eucheuma; Tripneustes; Gracilaria; Acanthophora; Coral reef